Improvement in Neuropathy Specific Quality of Life in Patients with Diabetes after Vitamin D Supplementation - Uazman Alam; Asher Fawwad; Fariha Shaheen; Bilal Tahir; Abdul Basit; Rayaz A. Malik (Journal of Diabetes Research)
Objective. To assess the effect of vitamin D supplementation on neuropathy specific quality of life (NeuroQoL) in patients with painful diabetic neuropathy. Methods. This prospective, open label study was conducted between June 2012 and April 2013. Patients with symptomatic diabetic neuropathy were given a single dose of 600,000 IU intramuscular vitamin D, and NeuroQol was assessed at baseline and at five follow-up visits every 4 weeks. Results. Of 143 participants, 41.3% were vitamin D deficient (vitamin D < 20 ng/ml). Treatment with vitamin D resulted in a significant increase in 25(OH)D (P<0.0001) and a significant improvement in the NeuroQoL subscale score for emotional distress (P=0.04), with no significant change in the other NeuroQoL domains of painful symptoms and paresthesia, loss of temperature and touch sensation, unsteadiness, limitation in daily activities, and interpersonal problems. There was a significant reduction in patient perception about foot problems on QoL of “quite a lot” (P<0.05) and “very much” (P<0.0001) with a significant reduction in the baseline response of having a “poor” QoL from 5.2% to 0.7% (P<0.0001) and an increase in the response of an “excellent QoL” from 1.5% to 7.4% (P<0.0001). Conclusion. Vitamin D is effective in improving quality of life in patients with painful diabetic neuropathy.